1999
DOI: 10.1606/1044-3894.1784
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation in Lasting Marriages

Abstract: This paper is based on research that explored how 120 spouses from a sample of 60 white, African American, and Mexican American marriages adapted over the life span of their relationships which included the early years prior to children, the child-rearing years, and the empty-nest years. Important dimensions of these relationships -conflict and its management, sexuality, intimacy, decision-making and satisfaction -were explored in semi-structured interviews with each spouse. Understanding how spouses adapt ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…Similarly, retrospective research has generally found that older couples report that their marital satisfaction has increased relative to their earlier child-rearing years (e.g., Deutscher, 1964;Mackey & O'Brien, 1999). However, both of these lines of research have been criticized on methodological grounds.…”
Section: Change In Marital Satisfaction During Middle Age: Cross-sectmentioning
confidence: 99%
“…Similarly, retrospective research has generally found that older couples report that their marital satisfaction has increased relative to their earlier child-rearing years (e.g., Deutscher, 1964;Mackey & O'Brien, 1999). However, both of these lines of research have been criticized on methodological grounds.…”
Section: Change In Marital Satisfaction During Middle Age: Cross-sectmentioning
confidence: 99%
“…Two studies from 1980 and 2000 on cohort marriages find that wives reported less marital happiness than husbands and revealed that while the marital happiness of wives has slightly increased, that of husbands has slightly declined (Amato et al 2003;Rogers and Amato 2000). Several studies confirm the finding that husbands are more satisfied with their marriages than their wives (Mackey and O'Brien 1999;Park 2000;Guo and Huang 2005;Tsang et al 2003). Yet, numerous studies reveal that there is no gender difference in terms of marital satisfaction (Brezsnyak and Whisman 2004;Bushman 1998;Moitinho 2000;Levenson et al 1993;Thomsen and Gilbert 1998;and Weisfeld and Stack 2002;Yelsma and Marrow 2003).…”
Section: Studies On Marital Satisfactionmentioning
confidence: 96%
“…Marital satisfaction is defined as an individual's overall subjective evaluation of the nature of his or her marriage, including the degree to which the person's needs, expectations, and desires are met (Gelles 1995). With respect to the pattern of marital satisfaction throughout the life of a marriage, research reports that marital satisfaction decreases during the early years of marriage because couples need to adjust to a new circumstance where they have to negotiate responsibility and encounter realities of marital life (Amato et al 2003;Kurdek 1998;Mackey and O'Brien 1999). Marital satisfaction also declines when couples become parents due to losing positive perception about marriage by stressors of raising children (Lawrence et al 2008;Kurdek 1998;Leonard and Roberts 1998).…”
Section: Studies On Marital Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed comparisons would provide a better understanding of the predictors of marital satisfaction among older and middle-aged couples whose developmental tasks become more congruent over time (Carstensen et al, 1995) versus those older and middle-aged adults who are married to a significantly younger partner. It is imperative to examine these long-term relationships in order to provide a better understanding of those factors that have contributed to the success of these couples (Mackey & O'Brien, 1999). Closer examination of couples in longterm age-similar and age-discrepant marriages will provide a more comprehensive understanding of the developmental factors that affect marital interactions among partners as the "types" marital relationships continue to change in accordance with cultural shifts.…”
Section: Discussionmentioning
confidence: 99%